(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
An Electrical Resistivity Tomography (ERT) investigation was conducted at the Beduh earth dam in northern Iraq (Kurdistan Region) to identify leakage channels within the subsurface structure next to the dam body. The survey was conducted along four linear measurement traverses: traverses 1, 2, and 4 measured 300 meters each, while traverse 3 measured 200 m. All traverses were taken in the upstream part of the dam. Two traverses were located on the sides of the dam’s embankment, one was in the middle, and the fourth (Traverse 3) was perpendicular to them, running in a north-south direction parallel to the dam body. The examination of the inverted ERT sections indicated the presence of cracks, seepage paths, and karst phenomena within the limestone formations that comprise the top surface of the bedrock in the dam reservoir. Numerous subsurface structural abnormalities were identified within the fractured bedrock, predominantly linked to potential karstic cavities, voids, and discontinuities in the carbonate rocks. Furthermore, the results indicated the presence of a notable subsiding structure aligned with the main valley trajectory. It is posited that the highly fractured bedrock and other identified characteristics may be the main sources of water leakage from the dam’s reservoir.